2016
DOI: 10.1074/jbc.m116.715235
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Nuclear Receptor NR4A1 Binds a Novel Protein Interaction Site on Anti-apoptotic B Cell Lymphoma Gene 2 Family Proteins

Abstract: B cell lymphoma gene 2 (Bcl-2) family proteins are key regulators of programmed cell death and important targets for drug discovery. Pro-apoptotic and anti-apoptotic Bcl-2 family proteins reciprocally modulate their activities in large part through protein interactions involving a motif known as BH3 (Bcl-2 homology 3). Nur77 is an orphan member of the nuclear receptor family that lacks a BH3 domain but nevertheless binds certain anti-apoptotic Bcl-2 family proteins (Bcl-2, Bfl-1, and Bcl-B), modulating their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Furthermore, Dendrogenin A, a mammalian cholesterol metabolite ligand of liver-X-receptors (LCRs) induces Nr4a1 expression in association with excessive autophagic cell death both in vitro and in vivo [15,16], displaying anticancer and chemopreventive properties in mice [17]. Interestingly, NR4A1 interaction with anti-apoptotic BCL2 family members outside the BH3 domain induces autophagic cell death [18], which seems to be mediated by releasing BECN1 in a model of cigarette smokeinduced autophagic cell death [19]. Taken together, these findings indicate that NR4A1 could function as a broad inducer of autophagic cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Dendrogenin A, a mammalian cholesterol metabolite ligand of liver-X-receptors (LCRs) induces Nr4a1 expression in association with excessive autophagic cell death both in vitro and in vivo [15,16], displaying anticancer and chemopreventive properties in mice [17]. Interestingly, NR4A1 interaction with anti-apoptotic BCL2 family members outside the BH3 domain induces autophagic cell death [18], which seems to be mediated by releasing BECN1 in a model of cigarette smokeinduced autophagic cell death [19]. Taken together, these findings indicate that NR4A1 could function as a broad inducer of autophagic cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Dendrogenin A, a mammalian cholesterol metabolite ligand of liver-X-receptors (LCRs) induces Nr4a1 expression in association with excessive autophagic cell death both in vitro and in vivo (15, 16), displaying anticancer and chemopreventive properties in mice(17). Interestingly, NR4A1 interaction with anti-apoptotic BCL2 family members outside the BH3 domain induces autophagic cell death (18), which seems to be mediated by releasing BECN1 in a model of cigarette smoke-induced autophagic cell death(19). Taken together, these findings indicate that NR4A1 could function as a broad inducer of autophagic cell death.…”
Section: Introductionmentioning
confidence: 99%
“…NR4A1 was previously shown to regulate the transcription of cytochrome P450 C21 and C17 in rodents, consequently leading to the increased synthesis of cortisol and androgen, respectively 48,49. However, it also regulates the expression of genes involved in apoptosis or in the metabolism of progesterone (ie, AKR1C1) 36,50. Previously, NR4A1 was identified as a marker of luteolysis in the corpus luteum of cow and rat 36,37.…”
Section: Discussionmentioning
confidence: 99%
“…Although that binding was not perfectly matched, it is still possible that NR4A1 can induce the expression of AKR1C1. It was also found that NR4A1 can induce apoptosis by interacting with antiapoptotic proteins,50 suggesting that this factor can have additional roles in the porcine luteal tissue during regression. Interestingly, the expression of NR4A1 and couple other early response genes increase 30 minutes after PGF 2α injection in bovine midcycle corpus luteum, while 1.5 hours later plasma progesterone concentration decreases 52.…”
Section: Discussionmentioning
confidence: 99%